Enhanced electrical conductivity of polymer microspheres by altering assembly sequence of two different shaped conductive fillers. (October 2021) - Cho, Young Min; Lee, Sang-Soo; Park, Chong Rae; Kim, Tae Ann; Park, Min
Highlights: Core/shell conductive particles were prepared using Au nanoparticles and CNTs. Combination of 0-D and 1-D fillers facilitates the formation of conducting pathways. The assembly sequence of the conductive fillers affects overall electrical properties. Abstract: Conductive microspheres are prepared using two different shaped conductive fillers, carbon nanotubes (CNTs) and Au nanoparticles (AuNPs), by a dry particle coating (DPC) process and a self-assembly method. CNTs, which are one-dimensional conductive fillers, facilitate the formation of conducting pathways so that the zero-dimensional AuNP content can be significantly reduced to obtain electrical percolation from the conductive microspheres. Two fabrication methods are investigated: (1) the self-assembly of AuNPs followed by the DPC of the CNTs on polystyrene (PS) microspheres (t-PS/AuNP/CNT) and (2) the DPC of the CNTs followed by the self-assembly of AuNPs (PS/t-CNT/AuNP). In both cases, the electrical percolation of the conductive microspheres is achieved using a significantly lower amount of AuNPs (1 wt%), which is 17 times lower than that of samples prepared using only AuNPs (17 wt%). Interestingly, each sample exhibits distinct conducting behaviors with different amounts of AuNPs owing to the different hybridization structures of AuNPs and CNTs.